Job Satisfaction in Achieving Performance Quality Among Academic Staff and Its Relationship to the Level of Performance and Job Achievement at Al-Imam University College (Private) - Assistant Professor Dr. Abdul-Razzaq Abdullah Ibrahim (Proximus Journal Publishing, 2025)
The researcher employed the descriptive-analytical method, which aims to describe the phenomenon under study, analyze its data, explore the relationships between its components, and examine the perspectives presented. The study sample was randomly selected from academic staff in the departments of Al-Imam University College, totaling 172 individuals. An exploratory sample of twenty participants was excluded from the main study, as shown in the table below
Keywords: Job Satisfaction; Performance Quality; Job Achievement